Chlorophyll a, phytoplankton, zooplankton and environmental data from Potter Cove during summers 2010-2020 - Antoni, Julieta Silvina; Almandoz, Gaston Osvaldo; Schloss, Irene Ruth; Garcia, Maximiliano Darío
This dataset contains the Chlorophyll a concentration, phytoplankton abundance, phytoplankton biomass of the most representative taxa, micro and mesozooplankton abundance and sea surface temperature average. Data and samples for this study were obtained in Potter Cove(PC, 25 de Mayo/King George Island, South Shetland Islands, Antarctica, 62°14'S, 58°38'W) during consecutive austral summers (January to March) of 2010-2020, except for 2015 when samples could not be collected. Water samples for phytoplankton, microzooplankton, total suspended particular matter, and chlorophyll a (Chl-a), along with CTD data, were collected at three sampling stations: E1 (inner cove, 62.232 S; 58.666 W), E2 (62.232 S; 58.688 W) and E3 (outer of cove, 62.269 S, 58.713 W). Sampling was conducted mostly biweekly and monthly samples were collected in summer 2012. Fil: Antoni, Julieta Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina Fil: Almandoz, Gaston Osvaldo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina Fil: Schloss, Irene Ruth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de Tierra del Fuego; Argentina Fil: Garcia, Maximiliano Darío. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Gobierno de la Provincia de la Pampa. Ministerio Publico.; Argentina